ANALISIS DAMPAK PERUBAHAN TARIF PAJAK PENGHASILAN DI INDONESIA - Asrul Hidayat (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2014)
This study analyzed the impact of changes in income tax on tax rates taxable income and tax ratio and made recommendations for changes of individual income taxes rates, the study was conducted by using comparative method oftax ratio and taxable income before and after the change in income tax rates. To ensure that the tax rate is the main variable that affects income tax revenue, the author used regression method. The result showed that the reduction in income tax rates caused tax ratio fell, while taxable income rose. In order to optimize tax cpllection efforts, this study recommended reduction of tax relief. This policy would certainly be a burden to the low-income individual taxpayers. Howewer, to minimize the impact, the study recommended changes in taxable income layers and individual income tax rates in each of the layers. Layers changes were also intended to obtain a more optimal tax revenue from high income individual taxpayers. The results showed that the recommended individual income tax rate could increase the individual income tax revenue.